2017
DOI: 10.1097/fbp.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D1 and D2 receptor antagonists on the discriminative stimulus effects of methylendioxypyrovalerone and mephedrone in male Sprague-Dawley rats trained to discriminate d-amphetamine

Abstract: Psychopharmacology research has amassed substantial evidence for similarities between synthetic cathinones and other commonly abused psychostimulants. Few studies have utilized drug discrimination methods to investigate synthetic cathinones, and the precise neurochemical substrates underlying their interoceptive effects have not been examined. The present study assessed the involvement of D1 and D2 dopaminergic receptors in the stimulus effects of MDPV and mephedrone in rats trained to discriminate d-amphetami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Many cathinones fully substitute for the discriminative stimulus effects of MDMA; however, several do not. [45][46][47][48] Recently, it has been reported that chemical structure plays a role, such that compounds with no substitutions on the phenyl ring, pyrrolidinyl cathinones, and compounds with long alpha side chains produce less MDMA-appropriate responding, 13,49 which is in agreement with other studies indicating that the alpha side chain length 38 and 4-substitutions 37,49 predict activity of cathinones.…”
Section: Drug Discriminationsupporting
confidence: 87%
“…Many cathinones fully substitute for the discriminative stimulus effects of MDMA; however, several do not. [45][46][47][48] Recently, it has been reported that chemical structure plays a role, such that compounds with no substitutions on the phenyl ring, pyrrolidinyl cathinones, and compounds with long alpha side chains produce less MDMA-appropriate responding, 13,49 which is in agreement with other studies indicating that the alpha side chain length 38 and 4-substitutions 37,49 predict activity of cathinones.…”
Section: Drug Discriminationsupporting
confidence: 87%
“…It is interesting to note that MDPV fully substituted in rhesus monkeys trained to discriminate cocaine (Smith et al, 2017) and in amphetamine-trained rats (Harvey et al, 2017), but not in MDMA-trained rats (Harvey and Baker, 2016) or in mephedrone-trained rats (DeLarge et al, 2017). This finding suggests that at least some cathinones may produce strong psychostimulant effects, but may not have MDMA-like effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have evaluated MDPV for substitution in animals trained to discriminate other stimulants. Full substitution was observed with MDPV in rats trained to discriminate d-amphetamine (Harvey et al 2017) or cocaine (Gannon et al 2016;Gatch et al 2013), although only partial substitution was observed with MDPV in rats trained to discriminate MDMA (Harvey and Baker 2016).…”
mentioning
confidence: 99%